2004
DOI: 10.1128/jb.186.12.4025-4029.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Last Gene of the fla/che Operon in Bacillus subtilis , ylxL , Is Required for Maximal σ D Function

Abstract: ylxL was found to be the last gene of the fla/che operon in Bacillus subtilis and is cotranscribed with the gene for the flagellum-specific alternate sigma factor, D . The ylxL gene was disrupted by insertional mutagenesis, and the resultant mutant strain was found to be compromised for D -dependent functions.In Bacillus subtilis, the structural genes that encode the hook-basal body complex (HBB), several genes controlling chemotaxis, and the gene for the alternate sigma factor, D , are found adjacent to one a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…Likewise, the swimming behavior seen by the authors might have resulted from selection under conditions that favor swimming for swrA + revertants. In any event, our results agree with those of Werhane et al (2004) …”
Section: Biasing Cell Population Heterogeneity Requires Swrbsupporting
confidence: 92%
See 2 more Smart Citations
“…Likewise, the swimming behavior seen by the authors might have resulted from selection under conditions that favor swimming for swrA + revertants. In any event, our results agree with those of Werhane et al (2004) …”
Section: Biasing Cell Population Heterogeneity Requires Swrbsupporting
confidence: 92%
“…Like SwrA, SwrB does not resemble other proteins in the databases, and its mode of action in augmenting D activity, and whether it does so in a direct or indirect fashion, are unknown. Werhane et al (2004) have reported that a swrB (ylxL) mutation alone caused a severe reduction in D -directed gene expression (in contrast to the subtle effect we observed) but oddly only a modest defect in motility. This work was, however, conducted with a laboratory strain in which the allelic state of swrA was not assessed.…”
Section: Biasing Cell Population Heterogeneity Requires Swrbcontrasting
confidence: 80%
See 1 more Smart Citation
“…σ D protein levels are low in chains due to a failure to express the sigD gene, the penultimate gene in the 27 kb fla/che transcript (1, 96, 147). Transcript abundance decreases along the fla/che operon such that the position of the sigD gene is critical for bias and the number of ON cells in the population may be increased simply by moving the sigD gene forward in the operon, closer to the promoter (Figure 1B) (31).…”
Section: Flagellar Regulationmentioning
confidence: 99%
“…SwrB is a single pass transmembrane protein expressed immediately downstream of σ D in the fla/che operon (Figure 1B) (147). Mutation of SwrB specifically abolishes swarming motility and appears to reduce late class flagellar gene expression (72, 147).…”
Section: Flagellar Regulationmentioning
confidence: 99%